First-principles Fröhlich electron-phonon coupling and polarons in oxides and polar semiconductors - Verdi, C (2017)
The Fröhlich coupling describes the interaction between electrons and infrared-active vibrations at long wavelength in polar semiconductors and insulators, and may result in the formation of polaronic quasiparticles. Polarons are electrons dressed by a phonon cloud, which can strongly affect the electronic properties of the crystal. Despite their ubiquitous role in a broad range of technologies, first-principles investigations of the electron-phonon interaction in polar materials are scarce. In this thesis we develop a general formalism for calculating the electron-phonon matrix element in polar semiconductors and insulators from first principles, which represents a generalization of the Fröhlich model and can be used to compute the polar electron-phonon coupling as a straightforward post-processing operation. We apply this procedure to explore an important material for photovoltaics, the hybrid lead halide perovskite CH3NH3PbI3. In this case we show that the temperature dependence of emission line broadening is dominated by Fröhlich coupling. Our method is formulated in conjunction with an ab initio interpolation technique based on maximally localized Wannier functions, which allows to describe all forms of electron-phonon coupling on the same footing. We demonstrate the validity of this approach on the prototypical examples GaN and SrTiO3. Focusing on anatase TiO2, a transition metal oxide of wide technological interest, we establish quantitatively the effect of including the ab initio Fröhlich coupling in the calculation of electron lifetimes. The rest of the thesis is devoted to exploring the quasiparticle properties in doped oxides. In particular, we investigate angle-resolved photoemission spectra from first principles in doped anatase TiO2 by proposing a novel framework that combines our ab initio matrix elements, including the dynamical screening arising from the added carriers, and the cumulant expansion approach. We compare our results with experimental data, and show that the transition from a polaronic to a Fermi liquid regime with increasing doping concentration originates from nonadiabatic polar electron-phonon coupling. We further validate this mechanism by calculating angle-resolved photoemission spectra in the ferromagnetic semiconductor EuO.